The effect of service quality on satisfaction of service recipients at International Youth Centre / Anis Natasha Mohd Ariff - Mohd Ariff, Anis Natasha (Faculty of Business and Management, 2020)
The purpose of this study is to identify the effect of service quality on satisfaction of service recipients at International Youth Centre. The research is based on a sample of 105 respondents. The results show that empathy and tangibility have significant impact on satisfaction of service recipients of International Youth Centre. It involves the process of conducting the research such as determining the sample, the reliability and validity of questionnaire and including the research design, sampling technique, and data collection method also involving primary data, secondary sources and data analysis technique. The main objectives of this study is to study the relationship between SERVQUAL dimensions and satisfaction of service recipients at International Youth Centre as well as to study the most significant factor that has impact on service recipients at International Youth Centre. The strongest relationship is between tangibility and satisfaction of service recipients.